Development and evaluation of RADA-PDGF2 self-assembling peptide hydrogel for enhanced skin wound healing - Deptuła, M.; Sawicka, J.; Sass, P.; Sosnowski, P.; Karpowicz, P.; Zawrzykraj, M.; Wardowska, A.; Tymińska, A.; Dzierżyńska, M.; Pietralik-Molińska, Z.; Peplińska, B.; Zieliński, J.; et al. (Frontiers in Pharmacology, 2023)
Background: Wound healing complications affect numerous patients each year, creating significant economic and medical challenges. Currently, available methods are not fully effective in the treatment of chronic or complicated wounds; thus, new methods are constantly sought. Our previous studies showed that a peptide designated as PDGF2 derived from PDGF-BB could be a promising drug candidate for wound treatment and that RADA16-I can serve as a release system for bioactive peptides in wound healing. Based on that, in this work, we designed a new self-assembling hydrogel RADA-PDGF2, connecting both peptides by a sequence specific for neutrophil elastase, and evaluated its activity in wound healing.The physicochemical properties of the designed scaffold were analyzed using TEM, AFM, cryoSEM microscopies, and circular dichroism spectroscopy. The enzymatic cleavage was performed using human neutrophil elastase and monitored using HPLC and MS spectroscopic techniques. The aforementioned techniques (HPLC and MS) were also used to assess the stability of the peptide in water and human plasma. The biological activity was analyzed on human skin cells using a colorimetric XTT test, collagen synthesis evaluation, and a migration assay. The biocompatibility was analyzed with LDH cytotoxicity assay and flow cytometric analysis of activation of immune cells. Finally, RADA-PDGF2 activity in wound healing was checked in a mouse dorsal skin injury model.The analysis showed that RADA-PDGF2 can self-assemble, form a hydrogel, and release a bioactive sequence when incubated with human elastase. It shows pro-proliferative and pro-migratory properties and accelerates wound closure in the mouse model compared to RADA16-I. In addition, it is not cytotoxic to human cells and does not show immunogenicity. RADA-PDGF2 seems to be a promising drug candidate for wound management.